Administrative practices related to Catholic school performance - Alvarez, Ma. Consolacion 1925-
This study investigated the relationship between school administrative practives in 22 Augustinian high schools in Luzon and the Visayas and school performance in terms of faculty morale, students' morale, parents' attitude towards the school and performance in the NCEE for three years. The responses of 22 principals, 241 teachers, 445 senior students, and 149 parents were analyzed utilizing the Spearman Rank Correlation and Multiple Correlation techniques. Teacher morale and NCEE performance are highly sensitive to administrative practices specifically academic and physical facilities administration. Success in the NCEE is largely determined by teacher competence, instructional materials and aids, and physical facilities.